Analisis Kualitas dan Kuantitas Air Permukaan Pasca Tambang (Pit Lake) di Tambang Emas Kabupaten Melawi - Aksa, Sukma Adi; Mulyadi, Achmad; Ruliyansyah, Agus (Department of Aquatic Resource Management, Faculty of Agriculture, Universitas Tanjungpura, 2026)
This study analyzes the quality and quantity of post-mining surface water (pit lake) in a former illegal gold mine in Sidomulyo Village, Melawi Regency, West Kalimantan. The objectives of the study were: (1) to assess water quantity (volume, depth, area), (2) to compare water quality based on physical-chemical parameters, and (3) to identify the use of pit lakes by the community. The study was conducted during June 2024–May 2025 in two pit lakes (Brown and Blue) with sampling in June and July. Water quality parameters included physics (temperature, brightness, TSS, TDS, color) and chemistry (pH, Cu, CN⁻, DO), analyzed using the Pollution Index (IP) and Water Quality Index (WQI) according to PP No. 22/2021 class III (fishery and agriculture purposes). The latest theoretical study integrates the concept of Acid Mine Drainage (AMD) (Kefeni et al., 2017). The quantity of Brown Pit Lake (volume 2,492.55 m³, depth 1.78 m, area 1,399 m²) and Blue Pit Lake (volume 19,458.80 m³, depth 3.41 m, area 5,705 m²) depends on rainwater. Brown Pit Lake IP: Good (IP 0.77 June) and Slightly Polluted (IP 1.28 July). Blue Pit Lake: Slightly Polluted (IP 2.69 June and 1.72 July). WQI: Both pit lakes have the status of